International briefing 27: Training and development in Peru - Velarde Talleri, Andrés (2012)
ABSTRACT Peru is in the central, western part of South America. It is the third largest country in South America and number 20 in the world. It is the country with the fourth highest population in South America. In 2010, the gross domestic product (GDP) of Peru was 154 billion USD, and its rate of growth was 8.8% (higher than the average for the region for the last 5 years). 56.8% of employed population was in the tertiary sector, 26.7% in the primary and mining sector and only 16.5% worked in manufacturing and construction. These figures are quite stable for the last years with a slight decrease in the primary sector (in 2006, it employed 32.9% of total employees), which went to the secondary sector (it was 14.2% in 2006) and the service sector (52.9% that year). In the period considered, employment has increased significantly in Peru due to economic growth. However, it is important to note that the rate of informality in the economy remains very high, with figures above 60%. The informal sector creates many "bad" jobs, without social insurance and other benefits normally provided by the formal sector. In this paper, the authors first describe the training and development policies; secondly, the higher and non-higher educational systems; finally, they display some statistics related to educational expenditure as well as Peru's strategic educational objectives.